Evaluation de la prévention du SIDA : rapport final. - Leurquin,P.; Renard, F.; Stroobant, A.; Tafforeau, J. (Bruxelles : Institut d'Hygiène et d'Epidémiologie, 1992)
Fonds Suzan Daniel (FSD)
Frans
Monografie